3D printing of hydrogel-based seed planter for in-space seed nursery. (September 2022) - Huang, Yanhua; Yu, Li; Jiang, Liangkui; Shi, Xiaolei; Qin, Hantang
Abstract: With the improved reliability and accessibility of 3D printing technology, interest in manufacturing parts using 3D printing became popular across academic and industrial sectors. Compared with traditional manufacturing approaches, it requires less facility and maintenance and provides the possibility of fast customization and modification at a lower cost. With the necessity of self-sustentation, growing plant in space is one of the most popular topics. Carboxymethyl cellulose hydrogel (CMC-gel) is one of the best candidates for sprouting substrate with 3D printing fabrication as it is non-toxic, biodegradable, and suitable for extrusion-based 3D printing. In this study, CMC-gel was designed and printed into different dimensions as soybean sprouting substrate. Soybeans were placed into the printed gel with different orientations. Upon 120 hours of sprouting without visible light, soybeans with hilum facing side had the highest water absorption average comparing those facing up or down. Across different hydrogels, hydrogel weight dominated the water absorption efficiency. These findings signified that bean orientation affects the sprouting process, and hydrogel weight can be further reduced upon 120 hours of the sprouting timespan. This study demonstrates the substrate geometry and seed orientation impacts on germination of soybeans, proposed guidelines for optimizing the sprouting process for high-level edible plants, and promoting innovated in-space seed nursery approach.